Design, manufacturing and preliminary assessment of the suitability of bioplastic bottles for wine packaging. (August 2021) - Aversa, C.; Barletta, M.; Gisario, A.; Pizzi, E.; Prati, R.; Vesco, S.
Abstract: The aim of this study is to evaluate the suitability of bioplastic bottles for wine packaging. The wine is largely packaged in glass bottles, although alternative solutions such as laminate, plastic and bag-in-box packaging are decidedly widespread on the market by virtue of their ease of use and low cost, especially for the so-called entry-level products. However, packaging involving the partial or exclusive use of plastic is the subject of discussion in the scientific community, by virtue of the persistence of plastic materials in the environment at the end of the product life cycle. A solution that could reconcile the practicality and low cost of plastic packaging with a reduced environmental footprint is the replacement of fossil-based plastics with compostable bioplastics. The latter biodegrade if properly treated at the end of their life, limiting the environmental footprint of the packaging. Bioplastics are, however, more complex to process than conventional plastics, also presenting a higher cost. The objective of this study is therefore the manufacture of prototype bottles in bioplastic for the packaging of wine by means of an extrusion blow molding process, as well as the evaluation of the main thermo-mechanical and physical properties of the same. Highlights: Evaluate the suitability of bioplastic bottles for wine packaging produced by extrusion blow molding. Replacement of fossil-based plastics with compostable bioplastics. Bioplastic biodegrade if properly treated at the end of their life, limiting the environmental footprint. Bioplastics are more complex to process than conventional plastics, also presenting a higher cost. Evaluation of the main thermo-mechanical and physical properties of bioplastic bottle.